Hubungan Pengetahuan dan Sikap terhadap Kejadian Anemia pada Remaja Putri di SMK PGRI 2 Kota Jambi - Haryanti, Dwi; Putri, Aninda Ayu; Susanti, Desy; Desilawati, Fitria (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the relationship between knowledge and attitudes towards the incidence of anemia in young women at SMK PGRI 2 Jambi City. This research is a quantitative study with a retrospective approach. The population in this study were young women at SMK PGRI 2 Jambi City in 2024 totaling 201 female students and a sample of 67 female students. The data collection technique used random sampling with data analysis using the chi-square test. The results of the study showed that there was no relationship between adolescent knowledge and attitudes and the incidence of anemia in adolescent girls at SMK PGRI 2 Jambi City.